2015
DOI: 10.1016/j.neulet.2015.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal-glial populations form functional networks in a biocompatible 3D scaffold

Abstract: Phone number: +44 (0) 0118 378 4745Postal address: School of Chemistry, Food & Nutritional Sciences and Pharmacy, University of Reading, Whiteknights, Reading, Berkshire, RG6 6AP, UK. AbstractMonolayers of neurons and glia have been employed for decades as tools for the study of cellular physiology and as the basis for a variety of standard toxicological assays. A variety of three dimensional (3D) culture techniques have been developed with the aim to produce cultures that recapitulate desirable features of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…ECM-LSEC and ECM gels, show a very low expression of adhesive and cohesive markers, with Connexin-32 being almost absent on adjunct-free ECM gels. Notably, cell nuclei were smaller and more rounded in the Matrigel-LSEC organoid, a typical feature of compact 3D tissue morphology [38,39]. …”
Section: Resultsmentioning
confidence: 99%
“…ECM-LSEC and ECM gels, show a very low expression of adhesive and cohesive markers, with Connexin-32 being almost absent on adjunct-free ECM gels. Notably, cell nuclei were smaller and more rounded in the Matrigel-LSEC organoid, a typical feature of compact 3D tissue morphology [38,39]. …”
Section: Resultsmentioning
confidence: 99%
“…Tissueengineered structures are typically made from soft and porous matrices to allow for sufficient passage and supply of oxygen and nutrients to the cells. Synthetic materials such as polycaprolactone, polyethylene glycol, and even polystyrene have been used as scaffolds for cell adherence and support [5,19,20]. Another method for scaffold-based neural cell culture provides cells with natural ECM proteins such as laminin or collagen [3,21,22].…”
Section: Methods For 3d Cell Culturementioning
confidence: 99%
“…As HMGEC cultured on ThinCert did not yield convincing results, we further tested Alvetex scaffolds allowing cells to proliferate three-dimensionally, thereby communicating more dynamically, 34 to differentiate in response to distinct stimuli 35,36 and to function in an appropriate microenvironment. 37,38 Histologic analysis demonstrated that HMGECs exhibited the same appearance regardless of their location within Alvetex.…”
Section: Discussionmentioning
confidence: 99%